2023
DOI: 10.3390/ijms241311225
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Psoriasis Care: Probiotics and Prebiotics as Novel Therapeutic Approaches

Abstract: Psoriasis is a chronic inflammatory skin disease with autoimmune pathological characteristics. Recent research has found a link between psoriasis, inflammation, and gut microbiota dysbiosis, and that probiotics and prebiotics provide benefits to patients. This 12-week open-label, single-center clinical trial evaluated the efficacy of probiotics (Bacillus indicus (HU36), Bacillus subtilis (HU58), Bacillus coagulans (SC208), Bacillus licheniformis (SL307), and Bacillus clausii (SC109)) and precision prebiotics (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…Furthermore, combination therapy consisting of probiotic administration alongside a decreased antibiotic dosage has demonstrated positive results in children [42]. In both AOM and SOM, the incorporation of probiotics such as Lactobacillus and Streptococcus strains to maintain homeostasis in the gut microbiome will help in decreasing antibiotic usage, thus reducing adverse events [50]. Much like in SNHL, studies have suggested that providing a combination therapy of probiotics with a decreased dose of antibiotics yields stronger outcomes than aggressive antibiotic treatment alone [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, combination therapy consisting of probiotic administration alongside a decreased antibiotic dosage has demonstrated positive results in children [42]. In both AOM and SOM, the incorporation of probiotics such as Lactobacillus and Streptococcus strains to maintain homeostasis in the gut microbiome will help in decreasing antibiotic usage, thus reducing adverse events [50]. Much like in SNHL, studies have suggested that providing a combination therapy of probiotics with a decreased dose of antibiotics yields stronger outcomes than aggressive antibiotic treatment alone [54].…”
Section: Discussionmentioning
confidence: 99%
“…Prebiotics are micronutrients that foster the growth and activity of a beneficial gut microbiome. They are shown to be useful in diseases affecting the GI system, immune system, and nervous system in humans [46][47][48][49][50][51]. Harmful microbes which stimulate the immune system can be decreased and the cytokine environment can be modulated with prebiotics.…”
Section: Prebioticsmentioning
confidence: 99%
“…In addition, the gut microflora changed favourably towards an anti-inflammatory profile. The probiotics used in the study were Bacillus indicus, Bacillus subtillia, Bacillus coangulans, Bacillus licheniformjis, and Bacillus clausii, while the prebiotics given to patients were fructooligosaccharides, xyloligosaccharides, and galactooligosaccharides [108].…”
Section: Sun C Et Al 2021mentioning
confidence: 99%
“…GM's impact extends beyond the gastrointestinal system, influencing various aspects of overall health. Understanding the GM's composition, functions, and factors is essential for unlocking its potential to maintain health and prevent diseases [ 4 ].…”
Section: Overview Of the Gastrointestinal Microorganismmentioning
confidence: 99%